TicTad: A Chatterbot for Learning Visual C# Programming based on Expert System - Vinothini Kasinathan; Aida Mustapha; Sonia Siow; Marshella Hopman (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
This paper presents TicTad, a Chatterbot on Visual C# Programming to help students who struggle with learning programming, or who wants to learn Visual C#. TicTad provides an efficacious way to memorize the concepts through an interactive gateway. This will decrease the time and effort needed to learn Visual C# as compared to traditional methods.